KOMUNIKASI MITIGASI PARTISIPATIF DALAM MENDORONG PERUBAHAN SOSIAL (STUDI KASUS KRISIS AIR BERSIH PULAU MARINGKIK) - Rousanfikr, Sava Arcadia (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2025)
The prolonged clean water crisis on Maringkik Island in East Lombok shows that technical solutions alone cannot overcome fundamental problems without a participatory communication approach. This study uses a participatory communication approach based on Paulo Freire's theory to analyze barriers, communication patterns, and community involvement in mitigating the water crisis. A descriptive qualitative approach was used to collect data through in-depth interviews, observations, and documentation from various parties, including the community, the village government, the BPBD, and the PDAM. The results showed that the communication used for mitigation on Maringkik Island is still one-sided, administrative, and unsustainable. There are no counseling, training, or discussion forums that actively engage the community. The main barriers include weak inter-agency coordination, minimal use of communication media, budget constraints, and the absence of local facilitators. The absence of dialogic, equal communication positions the community as objects of policy rather than subjects who participate in developing solutions. This research emphasizes the importance of implementing participatory mitigation communication to encourage critical awareness, community empowerment, and sustainable social change. Keywords: Mitigation Communication, Participation, Water Crisis, Social Change, Maringkik Island, Paulo Freire